Increased diversity of Malassezia species on the skin of Parkinson’s disease patients - Han, Xinyu; Bedarf, Janis; Proske-Schmitz, Sabine; Schmitt, Ina; Wüllner, Ullrich (Frontiers in Aging Neuroscience, 2023)
Background: Parkinson's disease (PD) is characterized by motor disorders and the composition of Lewy bodies (LBs) in the substantia nigra. Due to the lack of a definitive biomarker, the current treatments do not modify the progression of PD. Recently, researchers revealed lipid dysregulation and some potential volatile biomarkers of PD related to a unique odor from PD patients by metabolomics of sebum, which is supposed to cause a potential change for skin microflora. In this study, we identified the 4 Malassezia species in PD patients and compared them with healthy controls.We collected 95 sebum samples (47 PDs and 48 Controls) by cotton swabs and extracted the DNA. The identification of Malassezia species was performed by Nested PCR. Specific primers for each species were used to amplify corresponding yeasts in each sample.Results: M. restricta and M.globosa are the most common species for both groups. The prevalence of M. slooffiae and M. sympodialis were significantly higher in the PD group compared with controls (63.8% vs. 29.1% and 74.5% vs. 54.2% respectively), the binary logistic regression model further indicated that M. slooffiae (OR=9.358, p<0.001) was associated with PD. Moreover, the diversity of Malassezia species was significantly greater (3.5 vs. 2.9 species per individual, p=0.002) in the PD group.Conclusions: Based on our results, we preliminarily observed a change in Malassezia species incidence and diversity on the skin of PD patients, which could be associated with lipid dysregulation; meanwhile, it might also be a noninvasive biomarker for PD.